Time lapse in-hole electrical resistivity surveying during a shallow release of CO2 gas: Harvey, Western Australia. Issue 1 (1st December 2019) - Harris, Brett; Costall, Alex; Nguyen, Hoang; Michael, Karsten; Ricard, Ludovic; Freifeld, Barry; Avijegon, Arsham; Pethick, Andrew
Summary: An in-hole electrode array was installed and cemented behind a fibreglass casing in a vertical monitoring well as part of an in-situ laboratory test for CO2 migration in a shallow fault zone in Harvey, Western Australia. The array consisted of 32 electrodes spaced at 3 m intervals, located between 277 m and 370 m below ground level. The intention of the experiments was to assess the value of permanent in-hole electrical resistivity systems, during a shallow-release of CO2 . The distance between the monitoring and injection wells was close to 7 m. Food grade CO2 gas was injected through a perforated interval located between 336 m and 342 m below ground level. In the order of 100, 000 time-lapse dipole-dipole electrode quadrupole measurements were acquired during the experiment. There was a clear change in measurements at the depth of the injection interval during the release of CO2 gas. Results are being compared with seismic, pressure and temperature data from the monitoring and injections wells from periods before, during and after injection.